Predicting Paclitaxel Disposition in Humans With Whole‐Body Physiologically‐Based Pharmacokinetic Modeling - Qiang Fu; Xinxin Sun; Maryam B. Lustburg; Alex Sparreboom; Shuiying Hu (Wiley, 2019)
Paclitaxel is a commonly used drug in the treatment of multiple solid tumors, including cancers of the breast, lung, and ovaries. Despite the established exposure-pharmacodynamic relationships for paclitaxel, treatment is associated with wide interindividual pharmacokinetic variability that leads to unpredictability of the agent's clinical activity and toxicity. We hypothesized that physiologically‐based modeling approaches could be employed to predict the human pharmacokinetics of paclitaxel following administration of the approved Cremophor‐based formulation (Taxol). The model was developed from tissue distribution studies performed in mice and applied to plasma concentration‐time data obtained in adult cancer patients receiving Taxol at the approved dose and schedule (175 mg/m2 by a 3‐hour intravenous infusion), taking into account interspecies differences in physiological parameters. The final model adequately captured the observed concentrations in patients and allowed prediction of paclitaxel distribution profiles in multiple target organs and can be applied to further refine the chemotherapeutic treatment with a clinically important agent.